In‐situ synthesis, characterization, antibacterial and nanotoxicological evaluation of synthetic polyvinyl chloride leather containing copper nanoparticles (PVC/NPsCU 0 ) - Salazar, Robert (2017)
Disease transmitting microorganisms, such as bacteria, viruses and fungi, are the main causes of hospital‐acquired infections (HAI). This is the justification for the development of nanotechnology‐based new materials and, in particular, for the synthesis of antibacterial nanocomposites of the type polymer / antibacterial metal, which create surfaces with a large bacteria inhibiting activity. In the present work, antibacterial polymeric nanocomposites have been created by preparing polyvinyl chloride (PVC) from a resin emulsion as plastisol and synthesizing copper nanoparticles in‐situ within the polymer matrix. The methodology of the process includes the synthesis of a copper precursor, its dispersion by ultrasonic pulses, its stabilization and mixing with other PVC additives, in order to obtain chemical reduction during the gelation of the plastisols. Analysis of the PVC / NPsCu0 laminates by Energy Dispersive X‐ray Fluorescence (EDXRF), using the PyMca software 4.7.4, reveals that the importance of the PVC gelation time is related to the degree of reduction of ascorbic acid (AA) on Cu2 +. On the other hand, examination by Scanning Electron Microscopy (SEM) shows that the size of the NPsCu0 varies between 50 and 250 nm. Examination by X‐ray Diffraction (XRD) shows the partial polymer crystallization of PVC and the presence of Cu0. The antibacterial activity of the PVC / NPsCu0 laminates was confirmed by the disc diffusion method on Escherichia coli O157: H7; the average zone of inhibition was 9.7 mm, indicating a significant bactericidal effect on this strain. A nanotoxicological assay was carried out to evaluate the viability of the development of these polymeric nanocomposites. The cytotoxic analysis of the PVC / NPsCu0 nanocomposites in human peripheral blood cells concluded that the cytotoxic effect on healthy cells was less than 8%.